Immunological characterization and prognostic of colon cancer evaluated by angiogenesis-related features: a computational analysis and in vitro experiments - Fei Liu; Yi Wang; Leiming Xia; Chen Sun; Yun Li; Yunhong Xia (Discover Oncology)
Abstract Background Diseases are often caused by multiple factors, angiogenesis-related genes (ARGs) have been shown to be associated with cancer, however, their role in colon cancer had not been fully explored. This study investigated potential biomarkers based on ARGs to improve prognosis and treatment effect in colon cancer. Methods ARGs associated with colon cancer prognosis were identified using Cox regression analysis and LASSO analysis. Furthermore, a prognostic model was constructed in colon cancer based on the 3 ARGs, and its biological function were analyzed. We evaluated the differences in tumor immune microenvironment based on prognostic signature. Finally, cell experiments confirmed the function of genes in colon cancer. Results The prognostic value of ARGs in colon cancer patients has been comprehensively analyzed for the first time and identified 3 ARGs with prognostic values. A prognosis risk model was constructed based on 3 ARGs and its prognostic value was validated on an independent external colon cancer dataset. In colon cancer patients, this prognostic feature was an independent risk factor and was significantly correlated with clinical feature information of colon cancer patients. This feature was also related to the immune microenvironment of colon cancer. Cell experiments showed that high expression of TNF Receptor Superfamily Member 1B (TNFRSF1B) significantly promoted apoptosis and inhibited proliferation of colon cancer cells. Therefore, TNFRSF1B may become an important regulatory factor in the progression of colon cancer by participating in intracellular functional regulation. Conclusions This study constructed a prognostic risk model based on three ARGs and for the first time discovered that TNFRSF1B may become an important regulatory factor in cancer progression by participating in intracellular functional regulation.